Optimization of a microfluidic based electromagnetic energy harvester for shoe insoles. (November 2015) - Rahman, M M; Atkin, R; Kim, H
Abstract: This paper reports improved performance of the 4 th generation microfluidic based energy harvester by finding global optimization among various geometric parameters, resulting in the increase of power density by 6.89 times. Specifically, the power output was optimized by varying diameters and spans of a coil at different frequencies. To verify the optimization, a custom testing platform was constructed, which mimicked the periodic linear movement caused by a human foot. The final device produced total power of 455.77mW from a volume of 20×3.74×0.75cm 3, resulting in a power density of 8.13mW/cm 3 that was identified as one of the highest power densities among human-body-induced vibration based energy harvesters.